P Penyalahgunaan posisi dominan dengan predatory pricing melalui Project S di TikTok dalam perpektif hukum persaingan usaha - Rahman, Fuji Andi (Maliki Interdisciplinary Journal, 2024)
Dominant position is a condition where a business actor has the highest position or there is no significant competitor in the relevant market. In the business world, a dominant position is not prohibited. However, a dominant position can lead to negative behavior in the business world and result in behavior that is prohibited by Law no. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. For example, using a dominant position with the intention to limit the market for competing business actors by setting prices below market prices (predatory pricing). The research method used is normative legal research with a case approach and a conceptual approach, and obtains data from primary and secondary legal materials. Then it was analyzed by descriptive qualitative by collecting data after which it was described systematically so as to obtain clarity for problem solving. Then the formulation of the problem that is examined analyzes the abuse of TikTok’s dominant position through projects with predatory pricing based on business competition law and how the government protects domestic MSMEs from abuse of pricing of imported products on the TikTok shop platform. The research results show that TikTok, through Project S, collaborates with its parent company, Bytdance, which indicates that it has abused its dominant position by using a predatory pricing method that can harm domestic consumers and MSME players. The role of the government must take swift action to protect MSME players from the abuse of their dominant position by Tiktok. In this case KPPU and the Ministry of Trade by strengthening supervision and regulating regulations related to e-commerce so as not to harm the community and the state.